Evidence-Based Medicine for Ballistic Maxillofacial Trauma - Wamkpah, Nneoma S; Kimball, Abby; Pipkorn, Patrik (Facial Plastic Surgery, 2023)
Ballistic trauma is a serious health issue with significant costs to physical, psychosocial, economic, and societal well-being. It may be caused from firearms, explosive devices, or any other projectile forces, and is characterized by severe tissue loss and evolving tissue devitalization. This review covers mechanism, diagnosis, and management of ballistic maxillofacial trauma, specifically. Initial evaluation includes stabilization of airway, bleeding, and circulation, followed by assessment of other injuries. The overall degree of tissue damage is determined by intrinsic patient factors and extrinsic projectile factors. Management of ballistic injuries has shifted toward advocation for early operative repair with the advent of antibiotics and advanced techniques in maxillofacial reconstruction. Appropriate timing and method of reconstruction should be carefully selected on a case-by-case basis. While ballistic trauma research is limited to studies biased by institutional practices, areas for further study identified from current literature include guidelines directing timing of reconstructive surgery; thresholds for free tissue transfer; handling of retained projectiles; incidence of surgical complications; and clinical outcomes for computer-aided surgical repair of these highly destructive injuries.
Keywords: ballistic; projectile; gunshot wounds; maxillofacial trauma; facial injuries; free tissue transfer